Alleviation of Synovial Inflammation of Juanbi-Tang on Collagen-Induced Arthritis and TNF-Tg Mice Model - Wang, Tengteng; Jia, Qingyun; Chen, Tao; Yin, Hao; Tian, Xiaoting; Lin, Xi; Liu, Yang; Zhao, Yongjian; Wang, Yongjun; Shi, Qi; Huang, Chenggang; Xu, Hao; et al. (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that is primarily characterized by synovial inflammation. In this study, we found that a traditional Chinese decoction, Juanbi-Tang (JBT), JBT attenuated the symptoms of collagen-induced arthritis (CIA) mice and in tumor necrosis factor transgenic (TNF-Tg) mice by attenuating the arthritis index and hind paw thickness. According to histopathological staining of ankle sections, JBT significantly decreased the area of inflammation and reduced bone destruction of ankle joints in both these two types of mice. Moreover, decreased tartaric acid phosphatase-positive osteoclasts were observed in the JBT group compared with those found in the control group. We also revealed that JBT suppressed monocytes and T cells as well as the production of CCL2, CCR6, and CXCR3 ligands. We next used high-performance liquid chromatography to investigate the components and pharmacological properties of this classical herbal medicine in traditional Chinese medicine. Based on network pharmacology, we performed computational prediction simulation of the potential targets of JBT, which indicated the NF-kappa B pathway as its target, which was confirmed in vitro. JBT suppressed the production of pro-inflammatory cytokines including interleukin-6 (IL-6) and IL-8, and inhibited the expression of matrix metalloproteinase 1 in fibroblast-like synoviocytes derived from RA patients (MH7A cells). Furthermore, JBT also suppressed the phosphorylation of p38, JNK, and p65 in TNF-α-treated MH7A cells. In summary, this study proved that JBT could inhibit synovial inflammation and bone destruction, possibly by blocking the phosphorylation of NF-kappa B pathway-mediated production of proinﬂammatory effectors.